Citric acid assisted solid state synthesis of V2O3, V2O3/C and V2O3/graphene composites for Li‐ion battery anode applications - Petnikota, Shaikshavali (2020)
A series of V2O3, V2O3/C and V2O3/G composite powders are prepared by simply annealing the reaction mixture containing ammonium metavanadate (0.1 M), reduced graphene oxide (rGO, 0.1 M) and citric acid (CA, 0.0, 0.1, 0.3 and 0.5 M) at 500 °C for 8 h under Ar flow. A variety of characterization techniques are used to investigate the structural, physiochemical features and electrochemical performance of the powders. The reaction mixture without rGO led to the formation of V2O3 at 0.1 M of CA and V2O3/C at 0.3 and 0.5 M of CA. As anodes of lithium‐ion coin cell batteries, V2O3, V2O3/C and V2O3/G composite electrodes exhibit an increase in capacity with increasing concentrations of CA. The increase in capacity is mainly attributed to the carbonization of CA and the declining crystallinity of V2O3. V2O3/C and V2O3/G prepared at 0.5 M of CA outperformed all other control compounds. The V2O3/C and V2O3/G delivered reversible capacities of 585 and 420 mAh g−1 respectively, during the first cycle with a current density of 50 mA g−1. The respective capacities after few initial cycles continuously increased to 608 and 463 mAh g−1 at the end of the 100th cycle.